Analisis Kausalitas Antara Ketimpangan Pendidikan, Ketimpangan Pendapatan dan Kemiskinan di Indonesia - Nur Azmi Randa; Sri Ulfa Sentosa (Universitas Negeri Padang, 2020)
This study aims to find out the causal relationship between educational inequality, income inequality, and poverty in Indonesia. The data used are secondary data in the form of panel data from 2011 to 2018. Data analysis used is descriptive analysis and inductive analysis. In inductive analysis there are several tests, namely (1) Root Root Test (Unit Root Test), (2) Cointegration Test, (3) Optimum Lag Test, (4) Granger Causality Test, (5) Stability Test (Stability Test), (6) Variable Response Test (Impulse Response Finction), (7) Variance Decomposition Test. The results of this study indicate that: (1) There is a causal relationship between educational inequality and income inequality. (2) There is no causal relationship between inequality in education and poverty. (3) there is no causal relationship between income inequality and poverty. But there is a one-way relationship between income inequality and poverty.